A family study on primary blepharospasm. Issue 2 (17th January 2006) - Defazio, G; Martino, D; Aniello, M S; Masi, G; Abbruzzese, G; Lamberti, S; Valente, E M; Brancati, F; Livrea, P; Berardelli, A
Abstract : Background: Previous family studies provided evidence that blepharospasm (BSP) can aggregate in families but did not give accurate and reliable information on the characteristics and degree of familial clustering. Aim: To evaluate the proportion of familial and non-familial BSP cases, the clinical expression of dystonia within families, the inheritance pattern, and the extent of penetrance. Methods: The study was based on the examination of the first degree relatives of 56 probands with primary BSP. Results: The 56 families produced a potential population of 436 first degree relatives of whom 296 were alive and 233 were examined. The proportion of index patients with at least one first degree relative affected by BSP, or adult onset dystonia other than BSP, was 27%. There was a remarkable degree of phenotypic variability of dystonia within families. Similar segregation ratios were calculated for probands' siblings and children. Under the assumption of autosomal dominant transmission of adult onset dystonia, penetrance was about 20%. Conclusions: The findings of this family study are relevant for accurately counselling the families of patients with BSP and may help identify the most appropriate study design to explore genetic susceptibility in BSP.